Genome-wide sequencing reveals small nucleolar RNAs downregulated in cerebral cavernous malformations - Kar, Souvik; Bali, Kiran Kumar (Cellular and molecular neurobiology, 2018)
Cerebral cavernous malformations (CCM) are vascular malformations associated with abnormally dilated blood vessels and leaky capillaries that often result in hemorrhages. Despite recent advances, precise understanding of the cellular and molecular mechanism leading to the pathogenesis of CCM remains elusive. Emerging evidence indicates that small nucleolar RNAs (snoRNAs), belonging to the class of non-coding RNAs, may play a significant role as diagnostic markers in human diseases. However, there is no report till date that studied the role of snoRNAs in CCM biology. The objective of the current study was to identify snoRNAs associated with CCM pathogenesis. Using genome-wide small RNA sequencing, we identified a total of 271 snoRNAs reliably expressed in CCM. By applying additional statistical stringency, three snoRNAs (SNORD115-32, SNORD114-22, and SNORD113-3) were found to be significantly downregulated in CCM patient tissue samples (n = 3) as compared to healthy brains (n = 3). Deregulation of the selected snoRNAs was further validated by qRT-PCR. Further, cellular localization via in situ hybridization also confirmed robust reduction in the expression of SNORD115-32 and SNORD114-22 in CCM tissues as compared to the healthy controls. By applying high-throughput sequencing and cellular localization analyses, we report here for the first time the genome-wide expression profile of snoRNAs in CCM tissues and a robust downregulation of candidate snoRNAs in CCM conditions. Future studies should warrant the screening in large CCM patient cohorts and will be helpful in the development of potential biomarkers and improved clinical diagnosis.
Gesehen am 11.11.2019